Presence of mind: consubstantiality and extended cognition in Montaigne's writing - Oddy, N (2022)
This study investigates how the metaphysical notion of consubstantiality can be rethought fruitfully as a distinctively cognitive figure in Montaigne’s writing. It argues that the consubstantiality ‘allegory’ through which Montaigne secures his reader’s sense of authorial presence in the 'Essais' can be brought into dialogue with contemporary cognitive scientific theories of extended mind, in a way that does not foreclose the controversial sacramental implicatures of the term in its sixteenth-century French context. Using a combination of methods (close readings, philological analysis and word histories, Relevance Theory) and drawing on a range of materials from the early modern to the contemporary, the three chapters of the thesis demonstrate key affinities between i) Montaigne’s early modern sense of the mind’s ramification and extension into the material, technological and social environment, and ii) contemporary conceptions of 4E cognition. The interdisciplinary (or comparative) and transhistorical approach adopted in this study enables a reflection on consubstantiality as an ontological and discursive concept from a variety of interconnected points of view. Firstly, from the perspective of memory, which is considered within a premodern mentalité closely bound up in Humanist rhetoric and poetics, and in relation to the Essais as a technology of memory, an artificial extension of Montaigne’s biological mind and lifespan. I then explore the scope for reading Montaigne’s early modern ecological thought in tandem with contemporary theories of cognition, through the lens of ‘contexture’. By linking contexture to relevance, I explore the interpretative implications for reading consubstantiality as operating along a continuum between the literal and the metaphorical, the natural and the artificial, the secular and the sacred. The third perspective from which I consider my main topic is prosthesis. I argue that the linguistic, medical and discursive concept of prosthesis affords another means of thinking about memory, identity, extended mind and intertextuality in Montaigne’s writing; as I show, this differently-embodied perspective complements consubstantiality and sheds important light on Montaigne’s conception of how part, ‘membre’, or fragment relates to the whole. By reconceptualizing consubstantiality through extended cognition, this study not only builds on existing cognitive approaches to Montaigne, but also, in reassessing a notion at the heart of Montaigne’s writing project and pivotal to successive generations of readers’ sense of Montaigne’s enduring presence and relevance, engages a broader methodological reflection on interdisciplinary readings of texts from the past.